Unpacking Team Task Performance: The Role of Positive and Negative Network Ties - Edinger, Suzanne K. (Journal of Organizational Psychology, 2025)
To accomplish key objectives, organizations frequently rely on work teams. This study of social networks and team performance sought to make two distinct contributions to theory: simultaneously researching positive and negative networks and integrating a more interdisciplinary research perspective. I investigated how the closure of instrumental and expressive networks combined to predict team intellective and judgmental task performance. A total of 386 participants in 66 teams participated, with 33 teams in each of the two task performance conditions. I found that an expressive (social identification) network had no relationship with intellective task performance, and that the relationship of the instrumental networks (shared leadership and advice) to intellective task performance was dependent upon the density of the task conflict network. I also found that instrumental networks (shared leadership and advice) were unrelated to judgmental task performance, and that the relationship of an expressive network (identification) to judgmental task performance was dependent upon the density of the social loafing network. While the findings from the present study provide a solid foundation for future research, much work remains before we fully understand the complex relationship between social networks and team performance.